1987
DOI: 10.1007/bf00404420
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resistance to fowl cholera is linked to the major histocompatibility complex

Abstract: Chickens of the Iowa State S1 line have been selected for ability to regress Rous sarcoma virus-induced (RSV) tumors, humoral immune response to GAT (Ir-GAT), and erythrocyte antigen B. Sublines homozygous at the major histocompatibility complex (MHC), as well as F1 heterozygotes and F2 segregants, were tested for resistance to fowl cholera by challenge with Pasteurella multocida strain X73. Control of the response at high doses was associated in a preliminary study with Ir-GAT and response to RSV tumors. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The Major Histocompatibility Complex (MHC) is a cluster of genes which encodes cell-surface glycoproteins that are involved in antigen recognition in immune responses. The MHC, or the B-complex as it is called in chickens, is closely associated with individual differences in susceptibility to many poultry diseases, such as Marek's disease (Briles et al, 1982), Rous sarcoma virus (Plachy et al, 1992), fowl cholera caused by Pasteurella multocida (Lamont et al, 1987), coccidiosis (Bumstead and Millard, 1987;Caron et al, 1997) and salmonellosis (Cotter et al, 1998). Although information on the involvement of the B-complex in resistance to helminth infections is very limited, Wetherall and Groth (1992) have shown that in mice certain MHC haplotypes are associated with resistance to helminths.…”
Section: Discussionmentioning
confidence: 99%
“…The Major Histocompatibility Complex (MHC) is a cluster of genes which encodes cell-surface glycoproteins that are involved in antigen recognition in immune responses. The MHC, or the B-complex as it is called in chickens, is closely associated with individual differences in susceptibility to many poultry diseases, such as Marek's disease (Briles et al, 1982), Rous sarcoma virus (Plachy et al, 1992), fowl cholera caused by Pasteurella multocida (Lamont et al, 1987), coccidiosis (Bumstead and Millard, 1987;Caron et al, 1997) and salmonellosis (Cotter et al, 1998). Although information on the involvement of the B-complex in resistance to helminth infections is very limited, Wetherall and Groth (1992) have shown that in mice certain MHC haplotypes are associated with resistance to helminths.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune disease associations with HLA are sometimes reported for alleles at individual loci, but with few exceptions it is difficult to understand whether individual loci or other genes nearby are actually responsible for the observed effect. In the chicken, MHC-B haplotypes, until recently distinguished primarily by serological methods, display strong influences in several infectious diseases (1)(2)(3)(4)(5). Resistance to Marek's disease tumors was mapped to a gene, or genes, closely linked to serologically-defined MHC-B class I (as opposed to BG Ags) in analyses of rMHC-B haplotypes (6 -8).…”
mentioning
confidence: 99%
“…The chicken major histocompatibility complex (MHC) has been associated with resistance, susceptibility, and differential responses to vaccines (Bacon, 1987;Lamont et al, 1987;Lamont, 1989;Heller et al, 1991;Kaufman, 2008). MHC haplotypes were commonly defined by serological reactions based on BF (MHC class I) and BG (MHC class IV) antigens (Briles and Briles, 1982).…”
Section: Introductionmentioning
confidence: 99%